Prevalence and determinants of anemia among children aged from 6 to 59 months in Liberia: a multilevel analysis of the 2019/20 Liberia demographic and health survey data - Adugna, Dagnew Getnet; Kibret, Anteneh Ayelign; Aragie, Hailu; Enyew, Engidaw Fentahun; Dessie, Gashaw; Melese, Mihret; Simegn, Wudneh; Abebe, Endeshaw Chekol; Admasu, Fitalew Tadele; Dejenie, Tadesse Asmamaw (Frontiers in Pediatrics, 2023)
Abstract Background: Anemia is a serious worldwide public health issue that occurs in all stages of life but primarily affects young children and pregnant mothers. Although anemia has a significant impact on child health, its prevalence and determinants among children aged 6–59 months have not been yet studied in Liberia. Therefore, this study aimed to identify the prevalence and determinants of anemia among children aged 6–59 months in Liberia. Methods: The data was extracted from Liberia Demographic and Health Survey, conducted from October 2019 to February 2020. The sample was obtained using a stratified two-stage cluster sampling. A total weighted sample of 2524 children aged 6–59 months was included in the final analysis. Stata version 14 software was used for data extraction and analysis. A multilevel logistic regression model was employed to identify determinants of anemia. Variables with a P-value of <0.2 in the bivariable analysis were selected as candidates for multivariable analysis. In multivariable analysis, the adjusted odds ratios (AOR) with the 95% confidence interval (CI) were reported for the determinants of anemia. Results: The overall prevalence of anemia among children aged 6–59 months in Liberia was 70.8% [95% CI: 68.9%, 72.5%]. Of these, 3.4% were severely anemic, 38.3% were moderately anemic and 29.1% were mild anemic. Children aged 6-23 and 24-42 months, being stunted, children from households with unimproved toilet facilities, children from households with unimproved water sources and lack of media (television) exposure were significantly associated with higher odds of anemia. However, using mosquito bed nets, living in the Northwestern and Northcentral region were significantly associated with lower odds of anemia among children 6-59 months. Conclusion: In this study, anemia among children aged 6–59 months in Liberia was a main public health issue. Age of the child, stunting, toilet facility, water source, exposure to television, mosquito bed net use, and region were significant determinants of anemia. Therefore, it is better to provide intervention for the early detection and management of stunted children. Similarly, interventions should be strengthened to address unimproved water sources, unimproved toilet facilities, and lack of media exposure.